Community Pharmacists' Involvement in the Ordering and Interpretation of Laboratory tests in two South-western States in Nigeria - S.J, Showande; O.A, Olaifa (Indian Journal of Pharmacy Practice)
The focus of this exploratory study was to determine if community pharmacists order laboratory tests, why they order the tests, what type of tests they order and what they do with the outcome of such tests. Self administered pre-tested 34-item semi-structured questionnaire were used to carry out this study among the superintendent pharmacists' of registered pharmacy premises in two south-western states in Nigeria. Descriptive statistics (frequency and percentages), Mann-Whitney U and Kruskal-Wallis tests were used to appropriately summarize the data obtained. All the respondents who consented to take part had ordered laboratory tests for patients prior to this study. The types of invasive and non-invasive tests ordered, ranged from simple dipstick pregnancy test to more varied tests like: fasting blood glucose 24(36.9%), blood pressure measurement 58(89.2%), malaria parasite test 47(72.3%), full blood count 16(24.6%), widal reaction test 45(69.2%), urinalysis 10(15.4%) mantoux test 3(4.6%) and hepatitis B & C test 3(4.6%). Some of the perceived benefits derived from interpreting medical laboratory test results were patient trust and confidence in pharmacists 28(43.1%), job satisfaction and relevance to the community 8(12.3%) and revenue generation 5(7.7%). Community pharmacists in the two South-western states of Nigeria ordered various types of invasive and non invasive laboratory tests and interpreted the outcomes of such tests either alone or in conjunction with physicians. This aspect of the pharmaceutical care continuum could be harnessed to foster the collaboration between pharmacists and physicians and ultimately improve patient care.
Keywords: Laboratory Tests; Community Pharmacist; Point of Care Test; Nigeria